2017
DOI: 10.1155/2017/5054237
|View full text |Cite
|
Sign up to set email alerts
|

Objective Endoscopic Analysis with Linked Color Imaging regarding Gastric Mucosal Atrophy: A Pilot Study

Abstract: Objectives We aimed to determine whether linked color imaging (LCI), a new image-enhanced endoscopy that enhances subtle differences in mucosal colors, can distinguish the border of endoscopic mucosal atrophy. Methods This study included 30 patients with atrophic gastritis. In endoscopy, we continuously took images in the same composition with both LCI and white light imaging (WLI). In each image, the color values of atrophic and nonatrophic mucosae were quantified using the International Commission on Illumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…Whether the patient has HP infection or not, the RGB distribution of EGC differs from the surrounding mucosa. Another study with Lab mode revealed that LCI allowed clear endoscopic visualization of the atrophic border, whether it has an HP-infected or HP-eradicated status [20]. This result is similar with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Whether the patient has HP infection or not, the RGB distribution of EGC differs from the surrounding mucosa. Another study with Lab mode revealed that LCI allowed clear endoscopic visualization of the atrophic border, whether it has an HP-infected or HP-eradicated status [20]. This result is similar with our study.…”
Section: Discussionsupporting
confidence: 91%
“…LCI is advantageous for improving the visibility of neoplastic lesions and for the evaluation of background mucosa and inflammation, especially neoplastic lesions in ulcerative colitis and GIM [13][14][15][30][31][32][33]. This is the first report on the detection of GIM using LCI; however, our study has some limitations.…”
Section: Discussionmentioning
confidence: 88%
“…Linked color imaging is a color enhancement technology that provides slight color differences in mucosal color which are easy to recognize with sufficient brightness compared with BLI and BLI‐bright. The color difference around the atrophic border became significantly higher with LCI than with WLI regardless of H. pylori infection status . LCI identified diffuse redness of the fundus as a crimson red color (Fig.…”
Section: Iee For Diagnosis Of Kyoto Classification Of Gastritismentioning
confidence: 93%
“…The color difference around the atrophic border became significantly higher with LCI than with WLI regardless of H. pylori infection status. 52 LCI identified diffuse redness of the fundus as a crimson red color (Fig. 3A,B).…”
Section: Bli and Lcimentioning
confidence: 99%